1995
DOI: 10.1109/10.391164
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of brain electrical activity into microstates: model estimation and validation

Abstract: A brain microstate is defined as a functional/physiological state of the brain during which specific neural computations are performed. It is characterized uniquely by a fixed spatial distribution of active neuronal generators with time varying intensity. Brain electrical activity is modeled as being composed of a time sequence of nonoverlapping microstates with variable duration. A precise mathematical formulation of the model for evoked potential recordings is presented, where the microstates are represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
785
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 828 publications
(799 citation statements)
references
References 22 publications
12
785
0
2
Order By: Relevance
“…The most dominant scalp topographies appearing in the groupaveraged ERPs from each condition over time were found using a Kmeans cluster analysis (Pasqual-Marqui et al, 1995). The optimal number of clusters to describe the data set was identified using a modified Krzanowski-Lai criterion.…”
Section: Eeg Analysesmentioning
confidence: 99%
“…The most dominant scalp topographies appearing in the groupaveraged ERPs from each condition over time were found using a Kmeans cluster analysis (Pasqual-Marqui et al, 1995). The optimal number of clusters to describe the data set was identified using a modified Krzanowski-Lai criterion.…”
Section: Eeg Analysesmentioning
confidence: 99%
“…This method is independent of the reference electrode (Michel et al, 2001(Michel et al, , 2004) and insensitive to pure amplitude modulations across conditions (topographies of normalized maps are compared). A modified hierarchical clustering analysis (Michel et al, 2001;Pascual-Marqui, Michel, & Lehmann, 1995), the agglomerative hierarchical clustering (Murray, Brunet, & Michel, 2008) was used to determine the most dominant configurations of the electric field at the scalp (topographic maps). A modified cross-validation criterion was used to determine the optimal number of maps that explained the best the group-averaged data sets across conditions.…”
Section: Topographic Pattern Analysismentioning
confidence: 99%
“…Statistical smoothing was used to eliminate temporally isolated topographic maps with low strength. This procedure is described in detail in Pascual-Marqui et al (1995). Additionally, a given topography had to be present for at least 10 time frames (20 ms).…”
Section: Topographic Pattern Analysismentioning
confidence: 99%
“…Thus, we can interpret the eigenconnectivities as building blocks of dynamic FC with a contribution that varies across time. In contrast to the clustering approach employed in electroencephalography (EEG) microstate (Pascual-Marqui et al, 1995) and FC state analysis (Allen et al, in press), where stable EEG scalp topographies or wholebrain FC states are identified, we used PCA to identify the most abundant building blocks that reappear across time and subjects.…”
Section: Introductionmentioning
confidence: 99%